Role of Radiosurgery/Stereotactic Radiotherapy in Oligometastatic Disease: Brain Oligometastases - Mazzola, Rosario; Corradini, Stefanie; Gregucci, Fabiana; Figlia, Vanessa; Fiorentino, Alba; Alongi, Filippo (Frontiers in Oncology, 2019)
During the natural history of oncologic diseases, approximately 20-40% of patients affected by cancer will develop brain metastases. Non-small lung cancer, breast cancer and melanoma are the primaries that are most likely to metas-tasize into the brain. To date, the role of Radiosurgery/Stereotactic Radiotherapy (SRS/SRT) without Whole brain irra-diation (WBRT) is a well-recognized treatment option for patients with limited intracranial disease (1-4 BMs) and a life-expectancy of more than 3-6 months. In the current review, we focused on randomized studies that evaluate the potential benefit of radiosurgery/stereotactic radiotherapy for brain oligometastases. To date, no difference in overall survival has been observed between SRS/SRT alone compared to WBRT plus SRS. Notably, SRS alone achieved higher local control rates compared to WBRT. A possible strength of SRS adoption is the potential decreased neurocognitive impairment.